Effect of corneal cross-linking on biomechanical changes following transepithelial photorefractive keratectomy and femtosecond laser-assisted LASIK - Chen, Wen; Bao, FangJun; Roberts, Cynthia J.; Zhang, Jia; Wang, Chong; Li, XueFei; Wang, JunJie; Abu Said, Anas Ziad Masoud; Mayopa, Kevin Nguelemo; Chen, YaNi; Zheng, XiaoBo; Eliasy, Ashkan; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Purpose: To evaluate the change in corneal biomechanics in patients with postoperative ectasia risk when combining two common laser vision correction (LVC) procedures (tPRK and FS-LASIK) with cross-linking (in tPRK Xtra and FS-LASIK Xtra). Methods: A total of 143 patients were divided into non-cross-linked refractive surgery groups (non-Xtra groups, tPRK and FS-LASIK) and cross-linked groups (Xtra groups, tPRK Xtra and FS-LASIK Xtra) according to an ectasia risk scoring system. The eyes were subjected to measurements including the stress-strain index (SSI), the stiffness parameter at first applanation (SP-A1), the integrated inverse radius (IIR), the deformation amplitude at apex (DA), and the ratio of deformation amplitude between apex and 2mm from apex (DARatio2mm). The measurements were taken preoperatively (pre) and at 1, 3, and 6 months postoperatively (pos1m, pos3m, and pos6m). Posterior demarcation line depth from the endothelium (PDLD) and from the ablation surface (DLA) were recorded at pos1m. Results: SP-A1 significantly decreased, while IIR, DA, and DARatio2mm increased significantly postoperatively in all four groups (P < 0.01) – all denoting stiffness decreases. The changes in IIR, DA, and DARatio2mm in the FS-LASIK group and the changes in IIR in the tPRK group between pre and pos6m were larger (P < 0.05) than in the corresponding Xtra groups. The SSI experienced significant decreases only in FS-LASIK (P < 0.01), with minimal changes other groups(all p > 0.05). After correcting for baseline biomechanical metrics, preoperative bIOP and the change in central corneal thickness from pre to pos6m, the changes in the IIR in both FS-LASIK and tPRK groups, as well as DA, and DARatio2mm in the FS-LASIK group remained statistically higher than their corresponding Xtra groups (all P < 0.05). Moreover, after correcting for these covariates, the changes in DARatio2mm in the FS-LASIK Xtra became statistically smaller than in the tPRK Xtra (P = 0.017). Conclusions: The results indicate that tPRK Xtra and FS-LASIK Xtra effectively reduced the biomechanical losses caused by LVC. The decrease in corneal overall stiffness was greater in FS-LASIK than in tPRK, and the biomechanical enhancement of CXL was also higher following LASIK than after tPRK.